Addressing wear-resistant, bioactive, and bio-selective coatings on the biomedical Ti-6Al-4 V alloy by performing MAO treatment in TMO-rich electrolyte - Coan, Karine Stefany [UNESP]; Pereira de Sousa, Tiago dos Santos [UNESP]; Grandini, Carlos Roberto [UNESP]; Rangel, Elidiane Cipriano [UNESP]; da Cruz, Nilson Cristino [UNESP]; Barbaro, Katia; Fosca, Marco; Rau, Julietta V.; Tsipas, Sophia Alexandra; Nespeque Correa, Diego Rafael [UNESP] (Elsevier, 2025)
This study investigated the surface aspects of the Ti-6Al-4 V alloy submitted to micro-arc oxidation treatment (MAO) in an electrolyte enriched with bioactive species (Ca and P) and selected transition metallic oxides (TMOs) for potential use as biomedical implants. Adding some TMOs (TiO2, Al2O3, MoO3, Fe2O3, and MnO2) resulted in a thick and porous coating. Chemical analyses revealed the presence of Ca and P in a TiO2 matrix decorated with traces of Al, Fe, and Mo. FTIR, Raman, and XPS spectra indicated the formation of CO3 and PO4 groups bound to Ca and P. XRD profiles presented smooth peaks from TiO2 (anatase and rutile) and CaCO3. The TMOs slightly influenced Vickers microhardness, roughness, and wettability, while the wear resistance depicted a strong dependence. In vitro biological testing indicated that the growth and differentiation of mesenchymal cells were positively affected by the Ca and P, while the TMOs played a role in the growth of bacteria and fungi. TEM analysis uncovered some interlayers of the coating formed by the oxidative reactions and plasma discharges. The findings show that controlling the amount of TMOs in the MAO coating can be a valuable strategy for producing wear-resistant, bioactive, and bio-selective surfaces in Ti alloys.
Keywords: Biomaterial; Coating; Micro-arc oxidation; Surface; Ti-6Al-4V; TMO